The costs of interest representation – a resource perspective on informational lobbying. Issue 2 (May 2019) - Flöthe, Linda
Abstract: While expert information and information on public preferences are seen as key resources that interest groups provide to policymakers, little is known about the resources that are necessary to acquire such information. Existing scholarship argues that financial resources enhance a group's ability to supply information, which could be problematic as it suggests that resource poor groups are disadvantaged when lobbying policymakers. Applying a resource perspective to informational lobbying, this paper argues that different information types require different resources and that financial means are less important than assumed. The predictions are tested using a new dataset and survey of 383 advocates active on 50 specific policy issues in five West European countries. The results show that while economic resources are indeed associated with a higher amount of expert information, political capacities allow a group to provide both expert information and information on public preferences. This suggests that groups can rely on other than economic resources for information provision.